Adaptive Channel Selection Algorithm for a Large Scale Street Lighting Control ZigBee Network - Lavric, A.; Popa, V.; Sfichi, S. (Elektronika ir Elektrotechnika, 2013)
The present paper introduces an adaptive channel selection algorithm that can be integrated in a ZigBee network performing in an environment that is highly affected by IEEE 802.11 interferences. The algorithm can be implemented when a tree network topology is used. The interferences are detected by means of an ACK/NACK type algorithm. When interference is detected, each node of the network contributes to the selection of the optimum channel performance. A series of tests have been conducted in order to validate the performance of the suggested algorithm. Even when the RF environment is congested, the coordinator is able to make the optimum selection of the operating channel for the entire network. DOI: http://dx.doi.org/10.5755/j01.eee.19.9.5659